Nurses’ reports of working conditions and hospital quality of care in 12 countries in Europe - Aiken, Linda H.; Sloane, Douglas M.; Bruyneel, Luk; Van den Heede, Koen; Sermeus, Walter (International journal of nursing studies, 2013)
Cost containment pressures underscore the need to better understand how nursing resources can be optimally configured. To obtain a snapshot of European nurses’ assessments of their hospital work environments and quality of care in order to identify promising strategies to retain nurses in hospital practice and to avoid quality of care erosions related to cost containment. Cross sectional surveys of 33,659 hospital medical–surgical nurses in 12 European countries. Surveyed nurses provided care in 488 hospitals in Belgium, England, Finland, Germany, Greece, Ireland, the Netherlands, Norway, Poland, Spain, Sweden, and Switzerland. All nurses were surveyed from medical-surgical units 30 or more hospitals from geographically representative samples of hospitals in each country, except for Ireland and Norway, where all hospitals were selected, and Sweden, where nearly all hospitals were included by sampling all medical–surgical nurses who were members of the Swedish Nursing Association. Percentages are provided for each of the nurse and hospital characteristics reported. There was wide variation across countries in the percentages of hospital nurses that were bachelor's prepared (range 0–100%), in patient to nurse average workloads (3.7–10.2) and skill mix (54–82% nurses). More than one in five nurses (11–56%) were dissatisfied with their jobs in most countries, and dissatisfaction was pronounced with respect to wages, educational opportunities and opportunities for advancement. Sizable percentages (19–49%) of nurses intended to leave their jobs, though the percentage that thought it would be easy to find another job varied greatly across countries (16–77%). Nurse concerns with workforce management and adequate resources were widespread. While most nurses did not give their hospitals poor grades on patient safety, many doubted that safety was a management priority. Nurses reported that important nursing tasks were often left undone because of lack of time, and indicated that adverse events were not uncommon. Nurse shortages can be expected when national economies improve unless hospital work environments improve. Wide variation in nurse staffing and skill mix suggests a lack of evidence-based decision making. Additional research is warranted on the impact of these variations in nurse resources on patient outcomes.